Algorithm for correcting the image depth map based on the points brightness and their distance from the observation point - S. I. Korotkevich; Yu. V. Minaeva (Вестник Дагестанского государственного технического университета: Технические науки, 2020)
Objective. Modeling the human head is a significant problem that arises in a wide variety of fields of science and technology. Existing active technologies for reconstruction and modeling of the object under study require expensive equipment and trained personnel. Methods. An alternative is to use passive methods that perform image processing using special mathematical algorithms. One of these methods is the stereo vision, which is based on the use of paired images taken simultaneously with several cameras positioned and calibrated in a certain way. However, a common drawback of stereo vision methods is the possibility of obtaining erroneous depth maps due to poorquality source images or incorrect camera and lighting settings. Results. Procedures were developed that use additional parameters of image points, which can be used to correct depth maps to avoid the appearance of defects. To achieve this objective, the existing mathematical software for processing photo and video materials is analyzed; methods for suppressing noise in the image, obtaining an image contour, as well as a method for obtaining a 3D object matrix based on changing the direction of illumination are proposed; the algorithm is tested on a test example. Conclusion. The developed technique should improve the quality of the depth map of the processed image and thus make the modeling procedures more efficient.